2021
DOI: 10.1039/d1fo02797b
|View full text |Cite
|
Sign up to set email alerts
|

circ01592 regulates unsaturated fatty acid metabolism through adsorbing miR-218 in bovine mammary epithelial cells

Abstract: The composition of fatty acids plays a key role in regulating milk flavor and quality. Therefore, to improve the quality of milk, it is particularly important to study the regulatory...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In living organisms, free FAs, generally with low concentration, are mainly bound to fatty acid-binding proteins [11,12]. In this case, FAs in vivo are usually produced by the degradation of deposited fat and basically do not contain VLFCAs, and mitochondrial β-oxidation is the primary way of FAO.…”
Section: The Significance Of Peroxisomal β-Oxidationmentioning
confidence: 99%
“…In living organisms, free FAs, generally with low concentration, are mainly bound to fatty acid-binding proteins [11,12]. In this case, FAs in vivo are usually produced by the degradation of deposited fat and basically do not contain VLFCAs, and mitochondrial β-oxidation is the primary way of FAO.…”
Section: The Significance Of Peroxisomal β-Oxidationmentioning
confidence: 99%
“…Interestingly, the tsRNA/miRNA/mRNA co-expression network revealed that SCD may be regulated by both tsRNAs and miRNAs (tRF-Gly-GCC-037, tRF-Gly-GCC-042, tRF-Gly-CCC-016, miR-218a, and miR-281b). A previous study on dairy cows found that miR-218 could be involved in unsaturated fatty acid metabolism through ELOVL5 [ 48 ]. ELOVL5 is one of the key enzymes in the synthesis of unsaturated fatty acids, and it has been widely reported to participate in the synthesis of long-chain unsaturated fatty acids in human [ 49 ], goat [ 50 ], fish [ 51 ], and pig [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fatty acids (FAs) can be divided into short-chain, medium-chain, long-chain, and very-long-chain FAs. According to the degree of unsaturation on the carbon chain, they are also divided into saturated FAs, monounsaturated FAs (containing one double bond), and polyunsaturated FAs (containing multiple double bonds) ( 6 , 7 ). As nutrition has developed, studies have found that FAs with double bonds in different positions have different nutritional value.…”
Section: The Protective Function Of N-3 Pufasmentioning
confidence: 99%